Psychosocial Determinants of Vegetable Intake Among Nepalese Young Adults: An Exploratory Survey - Pandey, Sujita; Budhathoki, Mausam; Yadav, Dipendra Kumar (Frontiers in Nutrition, 2021)
Background: Adequate intake of vegetables facilitates a healthy lifestyle. However, the majority of Nepalese young adults consume inadequate amount of vegetables per day. Objectives: We explored psychosocial determinants of daily intake of two or more servings of vegetables among Nepalese young adults using attitude, social influence, and self-efficacy (ASE) as a theoretical framework, extended with measures of habit and self-identity as additional constructs. Methods/Participants: A cross-sectional study through a web-based questionnaire survey was conducted among 461 Nepalese young adults aged 18–35 years old. Participants were recruited through convenience (snowball) sampling. A factor-based partial least square structural equation modelling was used for analysis. Results: The findings indicated that attitudes (β = 0.09, p = 0.029), social influence (β = 0.17, p < 0.001), habit (β = 0.24, p < 0.001) and self-identity (β = 0.30, p < 0.001) were significant factors influencing intention to eat two or more servings of vegetables per day. Further, self-efficacy (β = 0.10, p = 0.011), habit (β = 0.08, p = 0.034), diet (β = −0.10, p = 0.014), and place of residence (β = 0.11, p = 0.007) significantly influenced behaviour to eat two or more servings of vegetables per day. However, self-efficacy (β = 0.07, p = 0.062) did not significantly influence intention and self-identity (β = 0.06, p = 0.083), age (β = −0.02, p = 0.328), gender (β = 0.02, p = 0.350), and body mass index (β = −0.04, p = 0.209) did not significantly influence behaviour to eat two or more servings of vegetables per day. Conclusion: The study shows that attitudes, social influence, habit, and self-identity were significant factors influencing intention to eat two or more servings of vegetables per day. Further, self-efficacy and habit significantly influenced behaviour to eat two or more servings of vegetables per day. However, self-efficacy did not significantly influence intention and self-identity did not significantly influence behaviour to eat two or more servings of vegetables per day.